2016
DOI: 10.1080/00220388.2016.1208173
|View full text |Cite
|
Sign up to set email alerts
|

Stature, Skills and Adult Life Outcomes: Evidence from Indonesia

Abstract: ACL-2International audienceWe investigate the effect of height on earnings, occupational choices and a subjective measure of wellbeing among Indonesian men. We explore the extent to which height captures the effects of endowments set before entry in the labour market. Physical and cognitive skills, co-determined with stature early in life, do not explain much of the height earnings premium directly. Yet, human capital more broadly, including cognition, educational attainment and other factors related to childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 77 publications
3
24
0
Order By: Relevance
“…Among the relatively few studies conducted in developing countries, Lee and Zhao () found that in China, height is associated with higher life satisfaction only among migrants from rural to urban areas, while the effect is not significant for individuals residing in urban or rural areas. In contrast, Bargain and Zeidan () reported a positive effect of height on life satisfaction in Indonesia.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Among the relatively few studies conducted in developing countries, Lee and Zhao () found that in China, height is associated with higher life satisfaction only among migrants from rural to urban areas, while the effect is not significant for individuals residing in urban or rural areas. In contrast, Bargain and Zeidan () reported a positive effect of height on life satisfaction in Indonesia.…”
Section: Introductionmentioning
confidence: 87%
“…Since then the determinants of human height have been the subject of increased interest by social scientists (Borrescio‐Higa, Bozzolib, & Drollerc, ). The reason is that height is an important predictor of earnings (Böckerman & Vainiomäki, ; Case & Paxson, , ; Cinnirella & Winter, ), job productivity (Bargain & Zeidan, ; Lee & Zhao, ), health (Lundborg, Nystedt, & Rooth, ; Perelman, ; Whitley, Rasmussen, Tynelius, & Batty, ), human capital (LaFave & Thomas, ), cognitive and non‐cognitive social skills (Benz & Frey, ; Rietveld et al, ; van Praag & Ferrer‐i‐Carbonell, ), as well as marriage and career successes (Janson et al, ; Lindqvist, ; Pollet & Nettle, ; Stulp, Buunk, Verhulst, & Pollet, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are important given increasing evidence of the lasting impacts of stunting and slow growth in height early in life on overall physical, biological and cognitive development, school achievement, economic productivity and maternal reproductive outcomes (see review by Dewey and Begum, 2011). Additionally, given the established literature on the existence of a height premium (Persico et al, 2004;Case and Paxson, 2008;Vogl, 2014;Bargain and Zeidan, 2017), these results have important economic importance.…”
Section: Introductionmentioning
confidence: 95%